Nitrogen doses on soybean growth and Asian rust progress in two cultivars - de Ramos, Juliano Perlin; Andriolo, Jerônimo Luiz; Balardin, Ricardo Silveiro; Marques, Leandro Nascimento; Serafini, Pablo Tuzi; Stefanelo, Marlon Tagliapietra (Comunicata Scientiae, 2017)
The main goal of this study was to analyze the range of effects of nitrogen doses on Asian soybean rust (Phakopsora pachyrhizi Sydow) progress over two soybean (Glycine max Merril) cultivars. Two experiments were carried out in greenhouse and in the field, during the 2011/12 and 2012/13 crop years. In the greenhouse, plants were grown in sand in 2011/12 and in a mix of sand and soil in 2012/2013, and supplied with five N doses by dripping fertigation. In the field, the crop was fertilized with six nitrogen doses with broadcast applications. The pathogen was inoculated in all experiments. It was assessed the Area Under Rust Progress Curve (AURPC), defoliation, dry matter, total concentration of N in leaves, number of grains per plant, thousand grain weight and yield. In the greenhouse experiment, nitrogen rates increased the plant growth and the disease progress during the first year. In 2011/12 field assay, a slight decrease of rust progress and a slight increase in yield from 160 to 242 kg ha-1 were recorded. However, under favorable environmental conditions for Asian soybean rust, the increases in grain yield obtained by using high N rates on both cultivars were minor than the damage caused by the disease.